IOT and Agriculture Data Analysis for Smart Farm - S, Sowmyashree; Biradar, Arun (International Journal of Computer Sciences and Engineering, 2025)
IOT plays a important role in agriculture. IOT uses sensors which are capable of providing information about agriculture field. Smart farming is managing farms using technologies like IOT to increase the quantity and quality of products by improving yields of crops. Wireless sensor network are being proposed for watering of crops to increase the productivity and gives the new direction for research in agriculture and farming through a mobile application in a smartphone. Wisekar is used to detect the disease in crops and report the type of crop disease to the farmer. As Farmer is the backbone of our country this work help the farmers handle various operation wirelessly through mobile applications and providing smart agriculture to farmers.